Mitochondrial DNA replication and transcription - Montoya, Julio (Henry Stewart Talks, 2007)
Introduction to the mitochondrial genetic system, Features of mammalian mitochondrial DNA, Characteristics of mitochondrial genetics, Mitochondrial DNA replication: strand-displacement and strand-coupled models, Proteins involved in mitochondrial DNA replication, Mitochondrial DNA transcription, Isolation and mapping of mitochondrial RNA, Model of transcription and RNA processing, Regulation of mtDNA expression by thyroid hormones, Regulation of the mammalian mtDNA expression by mTERF phosphorylation
Reviewed at 2022/04/12